LBDNet interlaboratory comparison for the dicentric chromosome assay by digitized image analysis applying weighted robust statistical methods - Chaves Campos, Fabio Andrés (2024)
Purpose: This interlaboratory comparison was conducted to evaluate the performance of the Latin-American Biodosimetry Network (LBDNet) in analyzing digitized images for scoring dicentric chromosomes from in vitro irradiated blood samples. The exercise also assessed the use of weighted robust algorithms to compensate the uneven expertise among the participating laboratories. Methods: Three sets of coded images obtained through the dicentric chromosome assay from blood samples irradiated at 1.5 Gy (sample A) and 4 Gy (sample B), as well as a non-irradiated whole blood sample (sample C), were shared among LBDNet laboratories. The images were captured using the Metafer4 platform coupled with the AutoCapt module. The laboratories were requested to perform triage scoring, conventional scoring, and dose estimation. The dose estimation was carried out using either their laboratory calibration curve or a common calibration curve. A comparative statistical analysis was conducted using a weighted robust Hampel algorithm and z score to compensate for uneven expertise in dicentric analysis and dose assessment among all laboratories. Results: Out of twelve laboratories, one had unsatisfactory estimated doses at 0 Gy, and two had unsatisfactory estimated doses at 1.5 Gy when using their own calibration curve and triage scoring mode. However, all doses were satisfactory at 4 Gy. Six laboratories had estimated doses within 95% uncertainty limits at 0 Gy, seven at 1.5 Gy, and four at 4 Gy. While the mean dose for sample C wassignificantly biased using robust algorithms, applying weights to compensate for the laboratory’s analysis expertise reduced the bias by half. The bias from delivered doses was only notable for sample C. Using the common calibration curve for dose estimation reduced the standard deviation(s*) estimated by robust methods for all three samples. Conclusions: The results underscore the significance of performing interlaboratory comparison exercises that involve digitized and electronically transmitted images, even when analyzing non-irradiated samples. In situations where the participating laboratories possess different levels of proficiency, it may prove essential to employ weighted robust algorithms to achieve precise outcomes.